Bumetanide attenuates sevoflurane‐induced neuroapoptosis in the developing dentate gyrus and impaired behavior in the contextual fear discrimination learning test. Issue 11 (2nd October 2022) - Wei, Kai; Liu, Yiheng; Yang, Xiamin; Liu, Jin; Li, Yuan; Deng, Meng; Wang, Yingwei
Abstract: Introduction: Sevoflurane acts as a gamma‐aminobutyric acid subtype A receptor agonist and can induce widespread apoptosis of immature dentate granule cells in postnatal day 21 mice. The dentate granule cells of postnatal day 21 mice undergo a developmental stage when gamma‐aminobutyric acid (GABA) shifts from inducing the depolarization of neurons to causing hyperpolarization. However, it is unclear whether sevoflurane induces apoptosis of immature granule cells by facilitating the depolarization or hyperpolarization of neurons. Methods: We utilized bumetanide, an Na + –K + –2Cl − cotransporter isoform 1 (NKCC1) antagonist, to determine whether the NKCC1‐mediated GABA depolarization of neurons plays a role in sevoflurane‐induced neuroapoptosis. We also investigated whether sevoflurane exposure is related to long‐term cognitive dysfunction in postnatal day 21 mice and explored the possible protective effects of bumetanide. Results: Bumetanide attenuated the sevoflurane‐induced apoptosis of dentate granule cells in postnatal day 21 mice. Exposure to sevoflurane at postnatal day 21 mice did not affect their motor ability or anxiety level, and it had no effect on spatial learning or memory functions. However, sevoflurane exposure at postnatal day 21 impaired the pattern separation ability in the contextual fear discrimination test; bumetanide mitigated this effect of sevoflurane as well. Conclusion: Bumetanide attenuates sevoflurane‐induced apoptosis and is a promising prospect for protecting against anesthesia‐induced neurotoxicity in the developing brain. Abstract : Bumetanide attenuates sevoflurane‐induced apoptosis of granule cells in the dentate gyrus of postnatal day 21 mice. Exposure of mice to sevoflurane at postnatal day 21 does not affect their motor ability or anxiety level, and it has no effect on spatial learning or memory functions. Bumetanide alleviates sevoflurane#x02010;induced performance impairment in the contextual fear discrimination learning test.